Detection of mtDNA Mutations Using the Amplification Refractory Mutation System-Polymerase Chain Reaction Method in Type II Diabetes Mellitus Patients in Publich Health Center Poasia: Detection of mtDNA Mutations - Satriani Syarif; Titi Purnama; Asni Ramayana Tina; Ilma Septiana (STIKes Mandala Waluya Kendari, 2023)
Background: Diabetes Mellitus (DM) is a heterogeneous disease caused by hereditary and ecological factors. One form of diabetes mellitus that is related to genetic factors is type 2 DM. type 2 diabetec melitus caused by dysfunction of insulin secretion, due to the presence of inhibition in the production of Adenosine Triphosphate (ATP) necessary in the process of its secretion by cells β glands of the pancreas. The dysfunction is related to the mutation of A to G at the 3243rd nucleotide position of the mitochondrial DNA tRNA gene. The purpose of the study was to find out whether there was a heteroplasmic mtDNA mutation in the genes of respondents to type 2 diabetes mellitus using the ARMS-PCR method. Methods: The type of research used is descriptive research, the sample used in this study is a blood sample in respondents of type 2 diabetes mellitus. The method chosen in this study is the Amplification Refractory Mutation System (ARMS)-PCR Method which is a PCR application that uses a specific primer. Results: According to this study, 20 of the 20 samples evaluated using the ARMS-PCR method were positive for the heteroplasmic A3243G mutation, which is defined by the presence of DNA bands measuring 200 bp on both tubes. These pathogenic mutations are inherited maternally and can cause a variety of disorders. Conclusion: After analyzing all samples, this study has concluded that they all contain hetero plasma mutations. The suggestions provided in this study are expected to be useful for future researchers who employ samples from other public health centers and hospitals.